Metode Naïve Bayes Untuk Prediksi Waktu Produksi Mebel di UD. Wali Barokah Kartasura Sukoharjo Jawa Tengah - RM Abdul Dhohir Surya Kusuma; Dwi Remawati; Kumaratih Sandradewi (Journal of Information Technology, Computer Engineering and Artificial Intelligence (ITCEA), 2024)
Wali Barokah is one of the industrial furniture craftsmen (furniture) with the main material using teak wood. The development of the times has made many furniture entrepreneurs appear, making the competition between furniture craftsmen increasingly tight. One way for customers not to be disappointed is that business voters must serve customers according to the specified time when transacting. The attributes that will be used in classifying the production time are the name of the item, the number of orders, the difficulty, the equipment, the number of workers. The method that will be used is the the method Naïve Bayes Classifier. Based on the results of the confusion matrix test on the nave Bayes method of the dataset that has been taken on the object of research, an accuracy rate of 80% is obtained or is included in the category Good. Meanwhile, Precision is 83% and Recall is 88%.